The korean peace process and civil society - Kim, Dong Jin (Rethinking Peace and Conflict Studies, 2019)
The Post-Cold War era witnessed a dramatic rise in breakthroughs for peace processes, including the Korean peninsula, between parties mired in protracted conflict. However, many such processes broke down within a short period of time. This book explores the possibilities for comprehensive and sustainable peacebuilding strategy in the Korean peace process, beyond reaching an agreement, by reviewing diverse peacebuilding activities from government and civil society. Dong Jin Kim is Irish Research Council and Marie Skłodowska-Curie Actions Cofund CAROLINE Fellow at the Irish School of Ecumenics, Trinity College Dublin, Republic of Ireland. He is currently seconded to Corrymeela, Northern Ireland. Dr Kim's research focuses on sustainable peacebuilding in societies affected by protracted conflicts, such as Korea and Ireland.